Endemic plants of Java Island, Indonesia: a dataset - Dipta Rinandio; Hendra Helmanto; Rizmoon Zulkarnaen; Enggal Primananda; Arief Hamidi; Iyan Robiansyah (Biodiversity Data Journal, 2022)
Java is the most populous island in the world. This high population and the extensive economic activities have significantly reduced the forest areas of the Island and have greatly increased the pressure on its plant diversity. Compared to those with a wide distribution, endemic plants with a narrow geographic range are more vulnerable to anthropogenic threats and environmental changes. As species lists are essential for knowledge of species diversity in areas with strong anthropogenic pressure, here we present a dataset of endemic plants of Java Island. The initial species list was manually extracted from the Plant of the World Online (POWO). Each species on the list was then confirmed for its endemism by checking its current distribution using peer-reviewed publications, online plant databases and herbarium specimen images stored on the Global Biodiversity Information Facility (GBIF). The dataset contains 652 species in 279 genera and 85 families. The family with the highest number of endemic species is Orchidaceae (142 species), followed by Rubiaceae (57 species), Acanthaceae (40 species), Apocynaceae (35 species) and Lauraceae (29 species). The growth form of the species is mostly trees (22.6%), followed by herbs (19.2%), epiphytes (16%), shrubs (12.4%), vines (11%) and geophytes (9.4%). Most of the species (89.7%) have not yet been assessed for their conservation status according to the IUCN Red List Categories and Criteria. There are only 55 species (8.3%) that have been conserved within ex situ collections. Furthermore, most of the species (79.8%) are not listed on the CITES appendices and there are only four species (0.6%) protected by national law.Our contribution provides the first online list of accepted scientific names of Javan endemic plants species, together with all their synonyms. New to the dataset are: i) provision of local names of the species (if available), ii) the classification of species under eleven growth forms (tree, shrub, herb, annual, graminoid, geophyte, fern, vines, hydrophyte, parasite and epiphyte), iii) assignation of the extinction risk of species according to the IUCN Red List, iv) ex situ collection status of species and information on the protection status of the species according to (v) CITES and (vi) the national law of Indonesia.